2014
DOI: 10.3892/mmr.2014.1927
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of human umbilical cord-derived mesenchymal stem cells effectively relieves liver cirrhosis in DEN-induced rats

Abstract: Abstract.Cirrhosis is the long-term outcome of chronic hepatic injury and no effective therapy is currently available for this disease. Mesenchymal stromal cells (MSCs) are multipotent cells that are easily acquired and amplified, and may be potential candidates for cell therapy against cirrhosis. This study aimed to determine the therapeutic effects of human umbilical cord-derived MSCs (hUCMSCs) for the treatment of liver cirrhosis and identify an effective method for engrafting MSCs. The model of liver cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Nevertheless, researchers have investigated the effects of total MSC dose and dose splitting to determine an optimal therapeutic window. Hong et al (77) transplanted hUC-MSCs into rats with DMN-induced liver injury (0.01% supplemented diet given ad libitum for 4 wk) at varied doses, either as single infusions or as split dosing. They found that the antifibrotic effect was dose dependent, but probably not enhanced by split infusions (77).…”
Section: Does the Dose Of Mscs Matter?mentioning
confidence: 99%
“…Nevertheless, researchers have investigated the effects of total MSC dose and dose splitting to determine an optimal therapeutic window. Hong et al (77) transplanted hUC-MSCs into rats with DMN-induced liver injury (0.01% supplemented diet given ad libitum for 4 wk) at varied doses, either as single infusions or as split dosing. They found that the antifibrotic effect was dose dependent, but probably not enhanced by split infusions (77).…”
Section: Does the Dose Of Mscs Matter?mentioning
confidence: 99%
“…The latter zona pellucida glycoprotein is only expressed in oocytes (Lefièvre et al., ). Earlier studies reported ZP‐like structures surrounding OLCs differentiated in vitro (Hong et al., ). Singhal et al.…”
Section: Discussionmentioning
confidence: 92%
“…Hong et al. () reported that human follicular fluid stimulated differentiation into OLCs in vitro from stem cells. However, the differentiation of OLCs from ovarian stem cells isolated from adult bovine ovaries has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the involvement of MSCs in liver regenerative medicine, many studies have demonstrated that the infusion of human umbilical cord-or cord blood-derived MSCs via a vein or multiple direct injections into the liver effectively relieves liver cirrhosis and improves the survival rate in rodent models. These studies also suggest that multiple infusions show better clinical outcomes as compared to a single infusion of allogeneic MSCs [62][63][64][65].…”
Section: Allogeneic Stem Cells In Liver Cirrhosis Therapymentioning
confidence: 87%